Metal-Organic Frameworks: A Potential Platform for Enzyme Immobilization and Related Applications - Xia, Huan; Li, Na; Zhong, Xue; Jiang, Yanbin (Frontiers in Bioengineering and Biotechnology, 2020)
Enzymes, as natural catalysts with remarkable catalytic activity and high region-selectivities, hold great promise in industrial catalysis. However, applications of enzymatic transformation are hampered by the fragility of enzymes in harsh conditions. Recently, metal–organic frameworks (MOFs), due to their high stability and available structural properties, have emerged as a promising platform for enzyme immobilization. Synthetic strategies of the composites mainly including surface immobilization, covalent linkage, pore entrapment and in situ MOF synthesis are discussed. Compared with free enzymes, most immobilized enzymes exhibit enhanced resistance against solvents and high temperatures. Besides, numerous enzyme-MOF composites show extraordinary superiority in many aspects compared with other supporting materials. The advantages of using MOFs to support enzymes are discussed. To obtain a high enzyme loading capacity and to reduce the diffusion resistance of reactants and products during the reaction, the mesoporous MOFs have been designed and constructed. This review also covers the applications of enzyme-MOF composites in bio-sensing and detection, bio-catalysis, and cancer therapy, which is concerned with interdisciplinary nano-chemistry, material science and medical chemistry. Finally, some perspectives on reservation or enhancement of bio-catalytic activity of enzyme-MOF composites and the future of enzyme immobilization strategies are discussed.